Book Reviews (Uniting Church studies, 2025)
Jione Havea (ed.), Pacific Well-being: (Is)Lands, Theologies, Worldviews (Eugene, OR: Pickwick Publications, 2024), ISBN: 978-1-6667-6218-1). Reviewed by Te Aroha Rountree. Hanna Reichel, After Method: Queer Grace, Conceptual Design, and the Possibility of Theology (Louisville, KY: WJKP, 2023), ISBN: 978066426890. Reviewed by Geoff Thompson.